1990
DOI: 10.1093/jn/120.3.298
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Selenium-Dependent Glutathione Peroxidase by Perfluorodecanoic Acid in Rats: Effect of Dietary Selenium

Abstract: Forty-eight male Sprague-Dawley rats fed a diet containing 0.4, 0.2 or 1.0 mg of selenium (Se)/kg of diet were injected with a single dose (35 mg/kg) of perfluorodecanoic acid (PFDA) in corn oil and killed 2 wk later. Control animals were pair-fed and treated with an equal volume of vehicle. PFDA treatment significantly increased Se-dependent glutathione peroxidase (Se-GSHPx) activity in liver cytosol of rats fed the 0.04 mg of Se/kg of diet but not in rats fed the other diets. The increase in liver cytosolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…As expected, hepatic GSH levels were elevated in rats treated with a single dose of PFDA as in the previous report [14]. This response of GSH, however, was not uniformly observed in treatments with various peroxisome proliferators.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…As expected, hepatic GSH levels were elevated in rats treated with a single dose of PFDA as in the previous report [14]. This response of GSH, however, was not uniformly observed in treatments with various peroxisome proliferators.…”
Section: Discussionsupporting
confidence: 88%
“…Previously, we have shown that PFDA treatment significantly increased hepatic GSH levels in rats without significantly altering selenium-GSHPx activity [14]. The purpose of this study was to examine if PFDA treatment causes elevation of GSH in rat liver by altering the activities of enzymes that regulate GSH homeostasis.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Rats were fed a purified AIN-93 basal diet containing 0.2 ppm sodium selenate (Table 1; Harland Teklad, Madison, WI) and water ad libitum . A purified diet with a carefully controlled selenium level was chosen for this study, since previously we had observed that dietary selenium could directly influence the outcome of studies of the regulation of SeGPx (Chen et al 1990). After two weeks on the diet, rats were administered a single i.p.…”
Section: Methodsmentioning
confidence: 99%